1995
DOI: 10.1029/94jd00965
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and numerical modeling of radio sounding reflection from a lightning channel

Abstract: Electric field impulses and radar echo signal from lightning were measured synchronously. The measured electric field was used to calculate currents in return strokes which were used in numerical modeling of lightning discharge. On the basis of this simulation the radiowave reflection from a lightning channel was calculated. From the comparison of measured and computed radar echo signals the validity of the lightning discharge and the radiowave reflection numerical model was stated. Also, a continuous current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
2
11
0
Order By: Relevance
“…Assuming a 1 km long lightning, it corresponds to a 4 × 10 9 À10 10 W range which fits well in the middle of the 10 8 À10 12 W range measured in the visible from the satellite FORTE [Kirkland et al, 2001;Suszcynsky et al, 2000], knowing that 98% of events radiate less than 10 10 W according to Turman [1978]. Radiated energies in the three cases represent 20 to 25% of the total energy, in agreement with the computations of lightning discharges of Dubovoy et al [1995] and with the results of the first part of this article .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Assuming a 1 km long lightning, it corresponds to a 4 × 10 9 À10 10 W range which fits well in the middle of the 10 8 À10 12 W range measured in the visible from the satellite FORTE [Kirkland et al, 2001;Suszcynsky et al, 2000], knowing that 98% of events radiate less than 10 10 W according to Turman [1978]. Radiated energies in the three cases represent 20 to 25% of the total energy, in agreement with the computations of lightning discharges of Dubovoy et al [1995] and with the results of the first part of this article .…”
Section: Discussionsupporting
confidence: 82%
“…Radiated energies in the three cases represent 20 to 25% of the total energy, in agreement with the computations of lightning discharges of Dubovoy et al . [] and with the results of the first part of this article [ Ripoll et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in all cases treated between 15 and 40% of energy is radiated away, with a percentage between 20 and 25% for typical lightning energies. This is in agreement with Dubovoy et al [] but in disagreement with Paxton et al [], who reported as much as 69% of energy radiated [ Paxton et al , ]. We therefore confirm the criticisms of Hill [], who was the first to critique Paxton's apparent overestimation of the radiative losses.…”
Section: Discussionmentioning
confidence: 99%
“…In electrical engineering, there are three popular models of electric discharge: gas dynamics [8], electromagnetics [9], and distributed circuits [10]. However, none of these are directly applicable to visual simulation, as they respectively approximate the electricity as a cylinder of plasma, a thin antenna, and two plates in a circuit.…”
Section: Previous Workmentioning
confidence: 99%